2017
DOI: 10.1139/cjfas-2016-0290
|View full text |Cite
|
Sign up to set email alerts
|

Accounting for spatial complexities in the calculation of biological reference points: effects of misdiagnosing population structure for stock status indicators

Abstract: Misidentifying spatial population structure may result in harvest levels that are unable to achieve management goals. We developed a spatially explicit simulation model to determine how biological reference points differ among common population structures and to investigate the performance of management quantities that were calculated assuming incorrect spatial population dynamics. Simulated reference points were compared across a range of population structures and connectivity scenarios demonstrating the infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 49 publications
2
34
0
Order By: Relevance
“…Although regional management would be desirable because of possible trans‐border population processes, management strategies should also be versatile to account for spatial differences in life‐history traits. For instance, recent research shows that wrongly assuming spatial homogeneity may lead to depletion of less productive sub‐populations within a stock (Goethel & Berger, ). In this connection, we found that the annual cycle of the gonado‐somatic index of C. bajad from Saudi Gulf waters differed considerably from the cycle in Emirati waters of the southern Gulf.…”
Section: Discussionmentioning
confidence: 99%
“…Although regional management would be desirable because of possible trans‐border population processes, management strategies should also be versatile to account for spatial differences in life‐history traits. For instance, recent research shows that wrongly assuming spatial homogeneity may lead to depletion of less productive sub‐populations within a stock (Goethel & Berger, ). In this connection, we found that the annual cycle of the gonado‐somatic index of C. bajad from Saudi Gulf waters differed considerably from the cycle in Emirati waters of the southern Gulf.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier work has used simulations to evaluate possible consequences of disregarding independent population dynamics of identified genetic units within a management area (Goethel & Berger, 2017;Heath et al, 2014). Typically, the main concern is overexploitation of weaker components if spatial sub-structuring is disregarded (Bonanomi et al, 2015;Goethel & Berger, 2017;Kerr et al, 2017;Reiss et al, 2009).…”
Section: Assumption: Mixing Proportions Are Similar For Juveniles Amentioning
confidence: 99%
“…Spatially explicit population dynamics models are increasingly structured using multiple spatial strata (Goethel & Berger, ; Goethel et al, ). However, this approach requires extensive data to allow a fine spatial scale because (a) each stratum needs sufficient data so that model is tractable, and (b) additional data are often needed to estimate or predefine the connectivity among strata, for example movement.…”
Section: Discussionmentioning
confidence: 99%
“…These two types of model have fundamentally different structure, so have rarely been integrated into a single modelling framework. Consequently, natural resource management and conservation measures are often developed based on simplifying assumptions about, or implicit approximations to, population spatial structure, for example, management of marine fisheries resources (Goethel & Berger, 2017;Goethel, Quinn, & Cadrin, 2011;Punt, Haddon, & Tuck, 2015) and terrestrial wildlife (Adams et al, 2008;Bieber & Ruf, 2005). On the other hand, studies predicting effects of environmental changes have focused primarily on species' distributions (Ehrlén & Morris, 2015).…”
Section: Introductionmentioning
confidence: 99%